Kinematic and funtional analysis of rotator cuff exercise among Diyala University volleyball player with shoulder pain - Al Taie Mahmood Ali Mohammed (Tanjong Malim, 2024)
Kinematic and funtional analysis of rotator cuff exercise among Diyala University volleyball player with shoulder pain by Al Taie Mahmood Ali Mohammed